Melt processing of paramylon using a water:ionic liquid mixture as plasticizer. (15th April 2023) - Feuzing, Frédérica; Mbakidi, Jean Pierre; Pontoire, Bruno; Quéveau, Delphine; Roelens, Guillaume; Lourdin, Denis; Bouquillon, Sandrine; Leroy, Eric
Abstract: Paramylon is a linear β-1, 3-glucan produced by the microalgae Euglena Gracilis. Due to its native crystalline structure, involving hexagonally packed triple helices, paramylon is neither water soluble nor thermoplastic. While such properties are generally obtained by chemical modification of paramylon, the present work demonstrates that using ionic liquid/water mixtures as solvents or plasticizers may be an alternative: A mixture of water with cholinium glycinate (40:60) allowed: i) obtaining paramylon solutions at 80 °C, that form reversible ionogels upon cooling at 20 °C, when used as a solvent, and ii) the thermomechanical processing of paramylon below 100 °C by extrusion and hot-press into transparent films, when used as a plasticizer. The thermoplastic paramylon obtained consists of an amorphous matrix, self-reinforced by oriented triple helices packed as nanofibers. This results in a storage modulus ranging from 300 to 450 MPa at 25 °C, depending on the plasticizer content, and in a tensile strain at break of 27 %. For storage times larger than 1 month, a recrystallization of paramylon is observed, with an unidentified crystalline structure different from the native one. Recrystallized samples can be reprocessed into amorphous films by hot pressing.